SW and GB (N) ARQ Protocols under Markovian Interruptions - Khongorzul Dashdondov (Wireless Communications and Mobile Computing, 2018)
This paper discusses packet data multiplexing using stop-and-wait (SW) and go-back-N (GBN) automatic repeat request (ARQ) protocols under Markovian interruption. The Markov process shows the output channel by examining the Markovian interruption using inactive and active states. We assume that whenever the voice signal is active the output link is used and will be blocked for the data packet, and data traffic input is exponentially distributed in increments via the Poisson process, with each data packet transmitted within an individual time slot. Active and inactive periods of the original voice signal are geometrically distributed with their unique parameters. The study introduces the concept of average service time and average queueing delay to simplify the analysis and shows that data multiplexers using SW and GBN ARQ schemes exhibit queueing behaviour when the interruption signal follows a Markov process. Moreover, we derived the effective capacity that features the average arrival rate at the transmitter queue under the quality of service (QoS) constraints. Also from the results system stability depends on the error probability and Markovian interruptions occurrence. Simulation results verify the theoretical analysis.